2015
DOI: 10.1080/15377938.2014.936645
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Police Interactions and Disproportionate Minority Contact

Abstract: This study aims to uncover various aspects of police interactions that contribute to disproportionate minority contact with the juvenile justice system. In-depth interviews were conducted using a sample of 30 male juveniles residing in a correctional facility. The most consistent themes that arose included police allotting more chances to Whites than youth of color, repeated arrests by the same officer, police awareness of family reputations, and officers using unnecessary force against youth of color. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
1
25
0
2
Order By: Relevance
“…Although selective policing is highly debated and documented through extra-legal factors such as class, neighbourhood, gender and ethnicity (e.g. Feinstein, 2014;Holmberg, 1999;Holmberg & Kyvsgaard, 2003;McAra & McVie, 2005Pettersson, 2013Pettersson, , 2014, we are particularly interested in how young people themselves negotiate these factors their perceptions about (un)belonging.…”
Section: Perceptions Of Selective Police Stopsmentioning
confidence: 99%
“…Although selective policing is highly debated and documented through extra-legal factors such as class, neighbourhood, gender and ethnicity (e.g. Feinstein, 2014;Holmberg, 1999;Holmberg & Kyvsgaard, 2003;McAra & McVie, 2005Pettersson, 2013Pettersson, , 2014, we are particularly interested in how young people themselves negotiate these factors their perceptions about (un)belonging.…”
Section: Perceptions Of Selective Police Stopsmentioning
confidence: 99%
“…Social identity theory accounts for the power of this discriminatory behavior. Feinstein (2015) interviewed 30 male juveniles who resided in a correctional facility in Minnesota and found that youth of color were less likely to be treated fairly by police or to be given a second chance. She points out that police officers are still disproportionately white males, despite efforts to diversify policing in the USA.…”
Section: Survey Researchmentioning
confidence: 99%
“…This increases their chances of coming into contact with the police and having conflict with the police, which puts them at a greater risk for negative experiences of policing (Sindall, K., McCarthy, D. J., & Brunton-Smith, I., 2017) However, in today's society it is illegal for police officers to blatantly discriminate based on race, age, gender or any other characteristic of an individual. Despite this, discrimination still occurs in many indirect and direct ways primarily towards minorities who are at a disadvantage in society due to the inequality they continue to experience (Feinstein, 2015).…”
Section: Tablesmentioning
confidence: 99%
“…The decisions made at this initial point are crucial to the experiences of the public, for both adolescents and adults. Not only do police interactions determine whether individuals will be processed further through the criminal justice system, but they also shape the public's perceptions of police and their own relationship to society (Feinstein, 2015). Feinstein (2015) points out, "the frequency of police interactions alone influences perceptions of the police force.…”
Section: Race and Age As Mitigating Factorsmentioning
confidence: 99%
See 1 more Smart Citation